PENGARUH PROFITABILITAS, KEPEMILIKAN MANAJERIAL, KEPEMILIKAN INSTITUSIONAL DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN - subadriyah (UNSIKA (Universitas Singaperbangsa Karawang), 2020)
This researcher aims to test and analyze consisting of Profitability, Managerial Ownership, Institutional Ownership and Company Size of the Company Value of the basic & Chemical Industry Sector contained on the Indonesia Stock Exchange Period 2016-2018. The population of this study is the financial statements and annual reports from companies in the Industrial & Chemical Sector found on the Indonesia Stock Exchange Period 2016-2018. The sampling technique is purposive sampling so the number of samples is 11 companies. This study uses multiple linear regression data processing methods. The results obtained from this study partially Profitability variables affect the value of the company, while Managerial Ownership. Institutional ownership and company size have no effect on firm value. The variables of Profitability, Managerial Ownership, Institutional Ownership and Firm Size have a simultaneous effect on firm value.